Hoverflies are imperfect mimics of wasp colouration - Taylor, Christopher H.; Reader, Tom; Gilbert, Francis (Springer, 2016)
Many Batesian mimics are considered to be inaccurate copies of their models, including a number of hoverfly species which appear to be poor mimics of bees and wasps. This inaccuracy is surprising since more similar mimics are expected to deceive predators more frequently and therefore have greater survival. One suggested explanation is that mimics which appear inaccurate to human eyes may be perceived differently by birds, the probable agents of selection. For example, if patterns contain an ultra-violet (UV) component, this would be visible to birds but overlooked by humans. So far, indirect comparisons have been made using human and bird responses to mimetic stimuli, but direct colour measurements of mimetic hoverflies are lacking. We took spectral readings from a wide range of hoverfly and wasp patterns. They show very low reflectance in the UV range, and do not display any human-invisible colour boundaries. We modelled how the recorded spectra would be perceived by both birds and humans. While colour differences between wasps and hoverflies are slightly more distinct according to human visual abilities, bird vision is capable of discriminating the two taxa in almost all cases. We discuss a number of factors that might make the discrimination task more challenging for a predator in the field, which could explain the apparent lack of selection for accurate colour mimicry.